Juvenile hormone III induction reveals key genes in general metabolism, pheromone biosynthesis, and detoxification in Eurasian spruce bark beetle - Ramakrishnan, Rajarajan; Roy, Amit; Hradecký, Jaromír; Kai, Marco; Harant, Karel; Svatoš, Aleš; Jirošová, Anna (Frontiers in Forests and Global Change, 2024)
Introduction: In recent years, bark beetle Ips typographus, has caused extensive damage to European Norway spruce forests through widespread outbreaks. This pest employs pheromone-assisted aggregation to overcome tree defense, resulting in mass attacks on host spruce. Many morphological and behavioral processes in I. typographus are under the regulation of juvenile hormone III (JH III), including the biosynthesis of aggregation pheromones and associated detoxification monoterpene conjugates. Objectives, Methods: In this study, we topically applied juvenile hormone III (JH III) and performed metabolomics, transcriptomics, and proteomics in I. typographus both sexes, with focused aims:1. Highlight the JH III-regulated metabolic processes; 2. Identify pheromone biosynthesis-linked genes; and 3. Investigate JH III's impact on detoxification conjugates linked to pheromonal components. Results: Numerous gene families were enriched after JH III treatment, including genes associated with catalytic and oxidoreductase activity, esterases, phosphatases, and membrane transporters. Sex-specific enrichments for reproduction-related and detoxification genes in females and metabolic regulation genes in males were observed. On the protein level were enriched metal ion binding and transferase enzymes in male beetles. After JHIII treatment, mevalonate pathway genes, including terminal isoprenyl diphosphate synthase (IPDS), were exclusively 35- folds upregulated in males, providing evidence of de novo biosynthesis of pheromone components 2-methyl-3-buten-2-ol and ipsdienol. In addition, cytochrome P450 genes likely involved in the biosynthesis of cis/trans-verbenol, detoxification, and formation of ipsdienol, were 3-fold upregulated in the male gut. The increase in gene expression correlated with the heightened production of the respective metabolites. Detoxification conjugates, verbenyl oleate in the beetle fat body and verbenyl diglycosides in the gut, were induced by JHIII application, which confirms the hormone regulation of their formation. The JH III induction also increased the gene contigs esterase and glycosyl hydrolase up to proteins from male gut tissue. The esterase was proposed to release pheromone cis-verbenol in adult males by breaking down verbenyl oleate. The correlating analyses confirmed a reduction in the abundance of verbenyl oleate in the induced male beetle. Conclusion: The data provide evidence of JH III's regulatory role in the expression of genes and enzymes related to fundamental beetle metabolism, pheromone biosynthesis, and detoxification in Ips typographus.